A Bibliometric Profile of Green Criminology and its Reflections on Tourism - Banu Özüşen; Erkan Kadir Şimşek (Ceza Hukuku ve Kriminoloji Dergisi)
Green criminology is accepted as a sub-field of criminology and investigates threats against the entire ecosystem. The limited and unbalanced distribution of natural resources in the world and the rapid development of international trade has increased crimes against the elements of the ecosystem. This increasing number of crimes brings along multifaceted economic losses and health and safety issues for all living things. This study aims to use the bibliometric method to evaluate the research activities on green criminology, which has expanded its field of study since the 1990s and has become an interdisciplinary research field, by searching the studies on green criminology and discussing their reflections on tourism. This study uses the Scopus database to access a total of 360 documents published between 2010-2021. This study also examines the descriptive analysis results, annual scientific production, most cited publications, trending topics, most frequently used and related words, word cloud, tree map, three-field plot, world cooperation map, and cooperation network between authors and institutions. The study has determined 2020 to have been the most productive year regarding the number of publications. The article also investigates studies on the relationship between green criminology and tourism. The fact that only four studies are found on green criminology and tourism indicates the need for new studies in this context.